The effect of complementary therapies on parents' anxiety of children undergoing cancer treatment a systematic review - Tsitsi, Theologia; Raftopoulos, Vasilios; Charalambous, M. (My University, 2014)
To explore the effectiveness of Complementary and Alternative interventions in reducing stress in parents of children with cancer.
Keywords: Complementary and alternative medicine; Therapies; Cancer; Children